Towards Inclusion in Spanish Higher Education: Understanding the Relationship between Identification and Discrimination - Gallego-Noche, Beatriz (Social Inclusion, 2021)
It is more and more evident that there is diversity among university students, but this diversity encompasses a wide variety of personal characteristics that, on occasion, may be subject to rejection or discrimination. The feeling of inequality is the result of one stand‐alone characteristic or an intersection of many. To widen our knowledge of this diversity and to be able to design actions with an inclusive approach, we have set out to explore the relationship between students’ feelings of discrimination, their group identification and their intersections. Participants for the study are selected from protected groups which fall into the following criteria: ethnic minority, illness, migrant minority, disability, linguistic minority, sexual orientation, income, political ideology, gender, age and religion. We will refer to this relationship as the ‘discrimination rate.’ To fulfil our objective, we have given a questionnaire to a sample of 2,553 students from eight Spanish universities. The results indicate that the characteristics with which they most identify are religion, age, sex and political ideology. However, the highest rate of discrimination is linked to linguistic minority, ideology and migration. Regarding intersectionality, it is worth noting that 16.6% of students feel discriminated against for more than one characteristic, with the most frequent relationships being the following: (1) ethnic or migrant minorities (2) sexual orientation, sex, being under 30, leftist ideology, low income, linguistic minority and (3) Christian Catholic, right‐wing and upper‐class ideology.